BIOMASSA DAN KARBON POHON DI SEKITAR DANAU TAMBING PADA KAWASAN TAMAN NASIONAL LORE LINDU DESA SEDOA KECAMATAN LORE UTARA KABUPATEN POSO - Marjan, Marjan; Wardah, Wardah; Hapid, Abdul (Jurnal Warta Rimba, 2016)
Forest is an absorber of carbon that began to be a spotlight when the earth facing greenhouse effect. The greenhouse effect can be an increase of air temperature or commonly named global warming. The global warming is caused by the concentration improvement of the greenhouse in atmosphere where the improvement affects the change of radiation balanced so that the earth temperature increase. This research aims at identifying the number of biomass and tree carbon around Tambing Lake in Lore Lindu National Park. This research was conducted in Tambing Lake area in Lore Lindu National Park Sedoa Village, Lore Utara Sub-district Poso Regency for three months started from February to April 2014. The estimation of tree biomass is using indirect method or allometric equation built in TNLL area. The result of this research revealed that the total of biomass on tree diameter ≥ 30 cm on the lake buffer is 653 ton/ha and 72 ton/ha for diameter tree ≤ 5 cm, for diameter tree ≥ 30 cm outside lake buffer is 793 ton/ha and 120 ton/ha to diameter ≤ 5 cm. While the total content of carbon inside lake buffer to diameter tree ≥ 30 cm is 286 ton/ha and to diameter tree ≤ 5 cm is 32 ton/ha. The total content of carbon outside the lake buffer to diameter tree ≥ 30 cm is 356 ton/ha and to diameter tree ≤ 5 cm is 54 ton/ha. The total average of tree biomass around Tambing Lake is 810 ton/ha and the average of tree carbon is 364,5 ton/ha.Key words: Biomass, Carbon, Tree, Tambing Lake